Numerical simulation of soft brick unreinforced masonry walls subjected to lateral loads - Jayaprakash Vemuri; Syed Ehteshamuddin; Subramaniam Kolluru (Cogent Engineering, 2018)
Unreinforced soft-brick masonry structures comprise a large portion of buildings in earthquake prone regions of India. Recent earthquakes have extensively damaged such structures. Experimental and numerical studies on soft brick unreinforced masonry structures are scarce in literature. In this paper, numerical simulation of soft brick unreinforced masonry panels subjected to lateral loads is performed. At the panel level, the masonry structure is modelled using the micro modelling approach within a finite element framework. Monotonic load envelope curve is generated through a pushover analysis of the finite element model. The in-plane failure modes are identified, and the effect of aspect ratio and axial stress on failure is examined. Cyclic load analyses are performed on the finite element model to understand the complex hysteretic behaviour of unreinforced soft-brick masonry walls.